LEGAL ASSISTANCE FOR THE POOR TO REACH JUSTICE - Arliman S, Laurensius; Suryanef, Suryanef; Arif, Ernita; Sarmiati, Sarmiati (LPPM STIH Putri Maharaja, 2022)
Legal aid to the poor has a fairly important position in every criminal, civil and administrative justice system, including Indonesia. The concept of legal aid to the poor is related to a person's rights to exercise these rights, therefore legal aid is carried out by legal experts and experienced people in order to carry out their profession. The purpose of this study is to explain legal aid for the poor to achieve justice. This research uses normative legal research which is described descriptively. The results of the study explain that legal protection is an action or effort to protect the community from arbitrary actions by authorities that are not in accordance with the rule of law, to create order and peace, thus enabling humans to enjoy their dignity as human beings. There are ten rules related to legal aid to the poor, both at the constitutional level to the law, Internal Regulations that apply to the Supreme Court and Internal Regulations that apply to the Ministry of Law and Human Rights, as a pattern and legal standing for the provision of legal aid for the poor. poor people in Indonesia. The provision of legal aid to the poor is a form of justice for the poor. The concept of legal aid to the poor is related to a person's rights to exercise their rights under the same law.